Agility, sprint and vertical jump performance relationship in young basketball players - Cauševic, D.; Abazovic, E.; Mašic, S.; Hodžic, A.; Ormanovic, S.; Doder, I.; Covic, N.; Lakota, R. (Acta Kinesiologica, 2021)
This study aimed to examine the relation between agility, sprint ability, and vertical jump performance of young basketball players. Fifty (n=50) young basketball players (mean±SD: age = 12.63±0.95; height = 160.84±6.31 cm; body mass = 50.82±6.88 kg) participated in the study. The agility T-test and 505 test were assessed to determine agility, 10m and 20m sprint was measured to determine sprint ability and countermovement jump (CMJ) for jumping performance. The results of Pearson`s Product Moment Correlation analysis indicated large to very large relation between agility tests and sprint performance (r = 0.61 to 0.85); agility and jump performance (r = -0.64 to -0.67); sprint and jumping performance (r = -0.59 to -0.77). The results of the study suggest that agility, sprint, and jumping performance share common physical demands, therefore it is necessary to develop them during the training.